Comparison Of Indonesian Police With Asian Police (Japan, South Korea, And Singapore) - Edi Saputra Hasibuan (KRTHA BHAYANGKARA, 2025)
This study aims to analyze and compare the institutional structure, functions, and authorities of the Indonesian National Police (Polri) with those of three Asian countries: Japan, South Korea, and Singapore. This study is motivated by various problems still faced by the Polri, including declining public trust due to several cases of violence by officers, such as the death of Afif Maulana, the shooting of Gamma Rizkynata, and internal conflict between Polri members in South Solok. The research method used is a juridical-normative with a comparative approach, through document studies, regulatory analysis, and a review of the latest literature. The results show that the police systems in Japan, South Korea, and Singapore have advantages in terms of accountability, transparency, and a stricter internal oversight system compared to Indonesia. In addition, these three countries have also demonstrated consistency in maintaining the independence of officers and providing human rights-oriented training. Meanwhile, the Polri still faces challenges in terms of structural reform, strengthening ethical culture, and apparatus professionalism. Therefore, it is necessary to adopt best practices from these countries to strengthen the Indonesian National Police as an effective, professional and publicly trusted law enforcement institution.